Do We Swallow the Waste From Our Brain? - Leaston, Joshua; Kulkarni, Praveen; Gharagouzloo, Codi; Qiao, Ju; Bens, Nicole; Ferris, Craig F. (Frontiers in Neuroscience, 2021)
Ferumoxytol, an iron oxide nanoparticle, was infused into the lateral cerebroventricle of awake rats to follow its movement and clearance from the brain using magnetic resonance imaging. Within minutes the contrast agent could be observed accumulating in the subarachnoid space, nasal cavity, nasal pharynx, and soft palate at the back of the throat. In a subsequent study fluorescent quantum dots were infused into the brain of rats and within 15 min could be observed in the esophagus using microscopy. These imaging studies clearly show that these large nanoparticle tracers (∼20 nm in diameter) leave the brain through the nasal cavity and end up in the gut. There are numerous studies going back decades reporting the clearance of tracers put directly into the brain. While these studies show the slow accumulation of trace in the blood and lymphatics, they report only accounting for less than 50% of what was originally put in the brain.